Dérive bodies: labyrinths and narratives of the internet in The sun vanished (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
From a performative perspective, this article addresses the relationship between narrative and dramaturgy in contemporary theater based on the play The sun vanished (2023) directed by Janaina Leite. The aim of this study is to analyze narrative aspects of contemporary dramaturgy and the procedures of dérive as a device for scenic creation, both in displacement through the internet and through the city. The article also proposes a reflection about virtuality as a field/genesis of fabulations for scenic narration.
Keywords: narrative; dérive; contemporary dramaturgy; internet